Student Social Conflict Dramaturgy at Universitas Muhammadiyah Makassar - Nur, Syahban; Jumadi; Kamaruddin, Syamsu A. (CV. Literasi Indonesia, 2024)
This research aims to analyze and describe the occurrence of student conflict dramaturgy at Muhammadiyah University Makassar, to analyze and synthesize the mechanism of the student conflict dramaturgy process at Muhammadiyah University Makassar, and to design solutions for student conflict dramaturgy Unismuh Makassar. This type of research is qualitative research with a case study approach. The informants for this research were 22 informants. Data was found through field observations, in-depth interviews, and documentation. These data are developed by giving meaning to the data, interpreting, or transforming the data into narrative forms which then lead to findings that nuanced scientific propositions that ultimately reach conclusions. Based on the results of the analysis, it was found that student conflict dramaturgy was developed by the interests of alumni actors, self-actualization, regional symbols, individual differences, and even clashes of interests. The dramaturgical process of student conflict was based on the front stage, then the middle stage continues to the backstage, then normal activities (of Stage) and forms of conflict dramaturgy including, inter-individual conflict, inter-group conflict, political conflict, and the last one is the dramaturgical solution to student conflict at the Muhammadiyah University of Makassar through an emotional approach, mediation, and providing space for actor actualization.